Association between child marriage and high blood glucose level in women: A birth cohort analysis - B.K. Datta; A. Tiwari; L. Glenn (Elsevier, 2024)
Objectives: Child marriage prematurely forces girls (<18 years of age) to perform adult roles prior to physical and psychological maturity. Such precocious transitions to young adulthood can have consequences on their long-term health, however, limited work has examined such relationships to date. As such, this study examines whether child marriage is associated with the risk of having hyperglycemia, or high blood glucose, in adulthood. Study design: Observational study using repeated cross-sectional data. Methods: Using data from the 2015-16 and 2019-21 waves of the India National Family Health Survey, we matched 432,080 and 418,409 women, aged 20-49 years, by birth year and month to create birth cohorts. Fitting multivariable binomial and multinomial logistic models, we compared the odds of having hyperglycemia across groups by marriage age (i.e., before or after age 18 years) within respective birth cohorts. Results: We found that the adjusted odds of having high blood glucose among women married as children were 1.12 (95 % CI: 1.07-1.16) times that of their peers married as adults in the full-sample. The adjusted relative risks of having blood glucose levels higher than normal but lower than diabetic and diabetic ranges were 1.09 (95 % CI: 1.04-1.14) and 1.23 (95 % CI: 1.15-1.31), respectively, in comparison to blood glucose within normal range. These results were persistent across sub-groups of different birth cohorts. Conclusion: Our findings suggest that child marriage was associated with higher risk of having high blood glucose in women, later in life.